THE USE OF QUIZZIZ IN TEACHING READING COMPREHENSION FOR THE FIRST-GRADE STUDENTS - Tania Booy; Andi Samsu Rijal; Rizka Indahyanti (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2026)
This research examined the effectiveness of Quizizz in improving the reading comprehension of first-grade students at SMP N 05 Waesama Ambon. The research used a quantitative approach with a pre-test and post-test single-group design. The instrument was a multiple-choice reading comprehension test focusing on descriptive texts and observations focused on student attitudes, motivation, participation, and engagement during the learning process using Quizizz. The sample consisted of 31 students in the academic year 2025. (the research instrument was a reading test). The results showed an increase in students' reading comprehension. The mean pre-test score was 49.100, while the mean post-test score rose to 83.300. Statistical analysis using a paired samples t-test showed a significant difference, (2-tailed) value of 0.000 < 0.05, indicating a significant difference between pre-test and post-test results, which is included in the good category. These results imply that Quizizz was effective in improving students' reading comprehension.